Peru Mining Sector Diagnostic - World Bank (World Bank, Washington, DC, 2021)
The facts and events that have shaped the strengths of the Peruvian mining industry are well established. Private mining investment has flowed in during the last decade, making Peru the second most popular destination for mining investment in Latin America. Peru has increased its annual copper production five times from approximately half a million to two and a half million metric tons of fine copper, moving from being only a major producer of gold to becoming also the second largest producer of copper in the world. The mining sector needs to create the necessary conditions, within a context of social legitimacy, to move forward successfully with the development of an extensive mining project pipeline. The country now faces the challenge of improving the sector’s policies and management to guarantee its long-term contribution to the country’s sustainable development. The government also faces the major challenge of artisanal and small-scale mining formalization and elimination of illegal mining, which has destroyed Amazon jungle with mercury, especially in the Amazonian Madre de Dios region. The Mining Sector Diagnostic (MSD) is a tool that the World Bank has developed to analyze the rules and policies that exist in the mining sector and the gap between these rules and their implementation in practice. It reviews sector performance from the perspective of the three main stakeholder groups , and analyzes their priorities to improve mining sector performance.